Digital interventions in medication adherence: a narrative review of current evidence and challenges - Moon, Zoe; Walsh, Jane (Frontiers in Pharmacology, 2025)
Non-adherence to prescribed treatments remains a major challenge facing the healthcare system. Despite decades of research, interventions to improve adherence typically have not shown large or sustained effects on adherence and are rarely implemented. Digital technologies provide a potential platform to increase the reach and cost-effectiveness of adherence interventions, allowing them to be widely rolled out. Current evidence suggests that digital interventions can increase adherence, but results are mixed with many interventions failing to improve adherence. This is likely because whilst the included interventions all utilise digital platforms, they vary significantly in their design, content and delivery. Many interventions are not theory or evidence based, do not include patient or healthcare practitioner involvement or focus simply on providing reminders. Evidence suggests that well-designed interventions which are evidence-based, are personalised and maximise interactivity are more likely to be successful. These well-designed interventions hold promise for improving adherence at scale. This narrative review discusses the current challenges facing digital adherence interventions and describes barriers to implementation or adoption which need to be resolved. These include considering reach, accessibility, and acceptability, to avoid increasing existing health inequalities. It is also critical to consider the quality, safety and regulation of available apps and other digital tools, as well as investigating ways to enhance engagement and retention. Finally, some digital tools may require integration into existing systems or may necessitate training of relevant staff. Overall, digital interventions appear to be a promising tool for improving medication adherence, but further work is needed to optimise these tools.